Genetic variation in the small heterodimer partner gene and young-onset type 2 diabetes, obesity, and birth weight in U.K. subjects. - Mitchell, S; Weedon, M; Owen, K; Shields, B; Wilkins-Wall, B; Walker, M; McCarthy, M; Frayling, T; Hattersley, A (2003)
The orphan receptor small heterodimer partner (SHP, NR0B2) modulates the transcription activity of the MODY1 gene HNF4a. Mutations in SHP were found in 7% of Japanese obese young-onset type 2 diabetic patients and were associated with moderate obesity and increased birth weight. We investigated SHP in 1927 U.K. subjects, examining relationships with type 2 diabetes, obesity, and birth weight. Sequencing of the coding region of SHP in 122 obese, young-onset type 2 diabetic patients detected the polymorphism G171A. The polymorphism was not associated with diabetes in case control or familial association studies. The A allele (frequency 0.07) was not associated with obesity in type 2 diabetic subjects (n = 348), their parents (n = 272), or young nondiabetic adults (n = 925). However, the rare (<1%) AA homozygotes had a raised BMI in each cohort; this was significant when all cohorts were combined (Z score = 0.67 AA vs. -0.05 G/x, P = 0.02). There was no association with corrected birth weight in 382 normal babies, but the only AA baby was 4,069 g. Our study suggests that genetic variation in SHP is unlikely to be common in the predisposition to diabetes, obesity, or increased birth weight in U.K. Caucasians.